2019
DOI: 10.1158/1538-7445.sabcs18-gs4-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS4-04: Primary results of NSABP B-39/RTOG 0413 (NRG Oncology): A randomized phase III study of conventional whole breast irradiation (WBI) versus partial breast irradiation (PBI) for women with stage 0, I, or II breast cancer

Abstract: Background: Conventional WBI after lumpectomy for early-stage breast cancer decreases ipsilateral breast tumor recurrence (IBTR), yielding comparable results to mastectomy. Accelerated PBI appears effective in reducing IBTR by treating only the tumor bed area. As the majority of IBTR occur at or in the vicinity of the tumor bed, we hypothesized that PBI would be as effective as WBI in controlling IBTR. The primary aim of NSABP B-39/RTOG 0413 was to determine if PBI provides equivalent local tumor control post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 0 publications
1
42
0
1
Order By: Relevance
“…External beam RT is advantageous in that it does not require additional invasive procedures. However, some studies have suggested that APBI delivered with 3D‐CRT may have higher rates of toxicity . The increased toxicity observed in these studies may be attributed to the use of twice‐daily fractionation and/or larger treatment volumes (≥2 cm margins).…”
Section: Introductionsupporting
confidence: 89%
“…External beam RT is advantageous in that it does not require additional invasive procedures. However, some studies have suggested that APBI delivered with 3D‐CRT may have higher rates of toxicity . The increased toxicity observed in these studies may be attributed to the use of twice‐daily fractionation and/or larger treatment volumes (≥2 cm margins).…”
Section: Introductionsupporting
confidence: 89%
“…3 Moreover, several trials show that APBI may afford similar local control to whole-breast radiation among appropriately selected patients. [4][5][6][7][8][9] APBI techniques include external beam radiation therapy (3-dimensional conformal or intensity modulated RT), brachytherapy (intracavitary or interstitial), and intraoperative radiation therapy. 10 Brachytherapy-based techniques have the longest follow-up data, with largely favorable long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This regimen differs from the twicedaily fractionation to 34 to 38.5 Gy used by the National Surgical Adjuvant Breast and Bowel Project B39 and RAPID trials. 8,9 The selection of this dosing scheme was based on excellent preliminary tolerability and efficacy data from our institution 13,14 and others 15 and robust patient preference for the convenience of a once-daily fractionation scheme compared with twice-daily (70% vs 30%). 16 We expect local control with this convenient daily regimen to be similar to twice-daily fractionation with more putatively improved cosmesis than seen with twice-daily fractions, based on radiobiologic priniciples.…”
Section: Introductionmentioning
confidence: 99%
“…Dose prescription and dose constraints on OARs were taken from RTOG protocols 0413, 0617, and 0415 for the breast, lung, and prostate cases, respectively. [16][17][18] Table III contains all dose constraints used. A prescription of 60 Gy delivered in 2 Gy/fx over a total of 30 fractions was used for the lung patient.…”
Section: C1 Dose Prescription and Organs-at-risk Constraintsmentioning
confidence: 99%